Alcohol intake and risk of colorectal cancer: results from the UK Dietary Cohort Consortium. - Park, J; Dahm, C; Keogh, R; Mitrou, P; Cairns, B; Greenwood, D; Spencer, E; Fentiman, I; Shipley, M; Brunner, E; Cade, J; Burley, V; et al. (2010)
BACKGROUND: Epidemiological studies have suggested that excessive alcohol intake increases colorectal cancer (CRC) risk. However, findings regarding tumour subsites and sex differences have been inconsistent. METHODS: We investigated the prospective associations between alcohol intake on overall and site- and sex-specific CRC risk. Analyses were conducted on 579 CRC cases and 1996 matched controls nested within the UK Dietary Cohort Consortium using standardised data obtained from food diaries as a main nutritional method and repeated using data from food frequency questionnaire (FFQ). RESULTS: Compared with individuals in the lightest category of drinkers (>0-<5 g per day), the multivariable odds ratios of CRC were 1.16 (95% confidence interval (95% CI): 0.88, 1.53) for non-drinkers, 0.91 (95% CI: 0.67, 1.24) for drinkers with 5-<15 g per day, 0.90 (95% CI: 0.65, 1.25) for drinkers with 15-<30 g per day, 1.02 (95% CI: 0.66, 1.58) for drinkers with 30-<45 g per day and 1.19 (95% CI: 0.75, 1.91) for drinkers with >or=45 g per day. No clear associations were observed between site-specific CRC risk and alcohol intake in either sex. Analyses using FFQ showed similar results. CONCLUSION: We found no significantly increased risk of CRC up to 30 g per day of alcohol intake within the UK Dietary Cohort Consortium.